2019
DOI: 10.1177/0972262919869747
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Moderators in Linking Job Crafting to Organizational Citizenship Behaviour: A Study on the Indian Hospitality Sector

Abstract: The purpose of this article is to test the conceptual model that addresses the association between job crafting (JC) and organizational citizenship behaviour (OCB) and also highlights how mindfulness and trust influence the JC and OCB relationship of front-line employees in hospitality sector. The data for the present study was collected from 246 front-line employees of Delhi-NCR regions of northern India. In order to avoid common method variance effect, the data was collected in two phases, namely T1 and T2. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
10
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 49 publications
2
10
0
4
Order By: Relevance
“…Our second piece of data upholds results of previous studies that have confirmed the positive influence of JC on OCB [50][51][52]. Furthermore, when considered together with the non-influence of Motivation to donate on the OCB (unconfirmed hypothesis), it is interesting to note that being motivated to donate blood is probably not enough to ensure a level of engagement in OCB that will enable the association to flourish and evolve.…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…Our second piece of data upholds results of previous studies that have confirmed the positive influence of JC on OCB [50][51][52]. Furthermore, when considered together with the non-influence of Motivation to donate on the OCB (unconfirmed hypothesis), it is interesting to note that being motivated to donate blood is probably not enough to ensure a level of engagement in OCB that will enable the association to flourish and evolve.…”
Section: Discussionsupporting
confidence: 81%
“…Lastly, Demerouti et al [54] also employed the JD-R Model to corroborate that JC is a construct capable of fostering extra-role positive behaviors, which as we have said can be filed under OCBs (see also references [50,51]).…”
Section: Theoretical Frameworkmentioning
confidence: 63%
See 1 more Smart Citation
“…In addition to the talent of employees, organizations also expect certain discretionary work-related behaviour from employees, which is not part of their job requirements but which support one's psychological and social environment such as organizational citizenship behaviour (Cem-Ersoy et al, 2015). Organizational citizenship behaviour is the pro-social behaviour of an employee, which is discretionary and not part of the formal role that affects other employees and the organization (Srivastava and Pathak, 2020). The concept received increased attention from Mediating role of psychological ownership 1 researchers during the last three decades (Khaola and Rambe, 2020) and is considered a pivotal factor in the competitive business environment (Khaola and Coldwell, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Karena semakin tinggi fokus perhatian, maka semakin baik pula hasil yang diberikan kepada perusahaan (Dane & Brummel, 2014) dan (Morrow & Conger, 2018). Hal ini mendukung penelitian yang dilakukan (Srivastava & Pathak, 2020) dalam penelitian mereka yang menyatakan bahwa job crafting dapat dipengaruhi oleh mindfulness, karena mindfulness mendorong konsentrasi dan minat pada pekerjaan yang dapat membantu karyawan untuk mengeksplorasi cara-cara baru dan kreatif untuk meningkatkan pekerjaan mereka dan membuat pekerjaan lebih bermakna yang akan meningkatkan organisasi.…”
Section: Pengaruh Job Crafting Terhadap Mindfulnessunclassified